Evaluation of Lithium Battery Cycle Aging Based on Temperature Increase During Charging - Hanchi Hong; Yu Zhu; Luigi d’Apolito; Shuiwen Shen (Batteries)
This study investigates the temperature increase characteristics of lithium-ion batteries under various states of health (SOHs) and proposes an aging assessment method based on temperature increase. The analysis of experimental data reveals that temperature increase behavior varies across different locations on the battery, particularly at the center of its large surface area, as the battery ages. This study demonstrates that monitoring surface temperature increase can serve as an effective method for rapid SOH assessment and provides insights into performance degradation and electrode aging. Furthermore, this approach enables the preliminary diagnosis of battery health by tracking temperature changes, without requiring complex equipment, making it highly practical and suitable for widespread application. In addition, this study discusses the potential impact of lithium plating on temperature increase characteristics and its implications for battery safety.